Correlation between Visual Acuity, Inner Segment/Outer Segment Junction, and Cone Outer Segment Tips Line Integrity in Uveitic Macular Edema. (8th June 2015) - Tortorella, Paolo; D'Ambrosio, Enzo; Iannetti, Ludovico; De Marco, Federica; La Cava, Maurizio
Abstract : Purpose . To investigate the correlation between best-corrected visual acuity (BCVA), the foveal inner segment/outer segment (IS/OS) junction or ellipsoid portion of inner segment (EPIS/ellipsoid zone), and the cone outer segment tips (COST) line or interdigitation zone integrity in eyes with uveitic macular edema (ME). Method . A retrospective observational study involving all patients from January 2012 to December 2013 with uveitic ME was performed. All patients underwent BCVA using Snellen charts spectral-domain optical coherence tomography (SD-OCT) examination using Spectralis OCT (Heidelberg Engineering, Heidelberg, Germany). Results . Fifty-two eyes from 45 patients were included in this study. Multivariate analysis showed a negative correlation between BCVA and the central retinal subfield thickness (CST), the cystoid pattern of edema, and the interdigitation zone interruption. Univariate logistic analysis showed a strong correlation between the ellipsoid zone and the interdigitation zone integrity. Conclusions . The ellipsoid zone defect, the interdigitation zone interruption, and the CST are correlated with poor vision. Visual acuity is also strongly affected by the cystoid pattern. The interdigitation zone integrity appears to be the most important factor in the visual prognosis of uveitic ME.